Analisis Permasalahan Dalam Pendirian Gereja HKBP Laut Dendang - Geubrina, Pocut Puan; Sinurat, Ester; Pandiangan, Errason; Hutagalung, Galatia Valentin; R, Rohani; Kardiana, Elsa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
A place of worship is a very important component in a religion. Nothing can be called a religion without a clear worship system and a permanent place of worship. Christianity calls their place of worship a ‘Church’, which means a house where God and His people meet. The function of this church is to describe their faith by singing spiritual songs with the aim of worshiping or praising their God. The data analysis technique uses qualitative research as the data analysis method. This study uses a case study methodology to conduct qualitative research. The subjects studied in this case study approach. In fostering harmony between religious communities, there must be a gap between one and another. Regarding various social problems that contain the potential for conflict in the local community and can disrupt and harm various efforts to create harmony between religious communities, for example, residential areas that function as houses of worship are found in most of the districts/cities targeted by this study. Thus, it is important for all parties, including the government, religious figures, and civil society, to continue to strive to create harmony and mutual understanding, so that similar conflicts do not recur in the future. Multicultural education, interfaith dialogue, and fair law enforcement are some of the important steps that can be taken to build an inclusive and harmonious society.